HUMAN PSYCHOLOGY IN THE QUR’AN: A CRITICAL APPROACH - Nihat UZUN (Fırat University, 2019)
The Qur’ân is the final link of God’s address to the humankind which aims to orientate the reprobate humankind. The main goal of the Qur’an is to form the relationship between human and God in pursuance of His wish and wisdom. In doing so, the Qur’ân uses some elements like parables, cultural elements, literary inimitability (i’câz) and directing the humankind to think about God’s blessings and might. The Qur’ân’s addressing to the humankind leads some researchers to claim that the Qur’an introduces, examines and analyzes every aspect of humanbeing and that this is very natural in terms of its goals. Although the Qur’an talks about some aspects and qualifications of humanbeing, to us, it does not introduce, examine and analyze every aspect of it on the one hand, the aim of its talking about humanbeing is totally different on the other hand. The view that the Qur’an has almost the same content as the modern science of psychology does, is addressed by some researchers very commonly and the verses are understood and interpreted in accordance with this view incorrectly and by breaking their contexts. To us, all these struggles mean to walk on the wrong way, eventhough they have a good intention.